Stimulated Recall Interview (SRI): Teacher’s Self Reflection - Yetty Zainil (English Language Teaching and Research, 2018)
Many researchers have preferred to use questionnaire and interview only in their investigation, however Golato (2002) reports that the data from teachers’ perception and interview may or may not be accurate, as there is often a considerable gap between what people think they do and what they actually do (Tian & Hennebry, 2016). This paper presents the investigation on teacher code-switching from the point of view of teachers’ understandings and beliefs about effective language teaching and learning. The study was carried out in an EFL classroom in four junior high schools in Padang, West Sumatra, Indonesia where the teacher and the students share Bahasa Minang (L1) and Bahasa Indonesia (L2). Conversation analysis was used as a tool to investigate the function teachers’ code-switching and stimulated recall interviews with five teachers which focused on instances of code-switching. The analysis showed that although code-switching clearly helped teachers and students in the teaching and learning process, it was often done on an ad hoc basis. The use of stimulated recall interview provides a powerful insight into the way teachers code-switch in the classroom. The findings suggest the incongruence between what the teacher thinks and they do in practice and resulted in stimulated self-reflection which may help teachers to develop pedagogical self-reflexivity.Key words: Stimulated recall, self-reflection, EFL classrooms